Paradigma Individual Konstruksi Identitas dalam Desain Hibrid: Ilusi Dimensi Tunggal Identitas yang Bersifat Kolektif Studi Kasus: Desain Rumah Tionghoa Peranakan - July Hidayat (ITB Journal Publisher, LPPM ITB, 2009)
Since a period of Abdurrahman Wahid government in reformation era who eliminated the prohibition to celebrate and express Chinese culture, Chinese people in Indonesia as if try to reinvent their Chinese identity. They try to represent the identity through their material culture, including the residential design. But is there anything that so pure called 'Chinese identity ' since in its development history, the Chinese culture in Indonesia has been intervened by other local cultural spaces like in Java, colonist culture, including modern one which are intervening each others, until becoming its hybrid form right now, called Chinese peranakan. Ethnical collective identity and effort to homogenize it on the base of essential sameness in culture (culture core) are illusive because in fact there are various cultural ideology orientations in the Chinese peranakan culture in Indonesia. Hybrid design represents the existence of third social space which means representation system having non-categorical character: becomes Javanese and Chinese altogether, even hybrid but also at the same time not both. Through semiotic approach, it is found that the hybrid is intervention space between design patterns (langue), parole and specific context of consumer. The dialogue has created the individual paradigm in hybrid design approach. The dialogue between individual contexts at the end forms collective identity network. The system moves from inside outward. It is different with common logic that assumes collective identity forms the individual one, not on the contrary.